Regarding the bill payment of BRAC - Adex Corporation Ltd. (Brac University, 2023)
This record consists of general correspondence regarding the regarding the bill payment for supply installation, testing and commissioning of 415V,50Hz, TPN+PE sandwich copper type tested busber trunking system at BRACU new campus project of BRACU new campus project..